2015
DOI: 10.4149/bll_2015_082
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coenzyme Q10 on organ damage in sepsis

Abstract: OBJECTIVE: Investigating the effects of coenzyme Q10 on organ damage and survival on mice in cecal ligation perforation (CLP) model in sepsis. BACKGROUND: Coenzyme Q10 is an antioxidant molecule playing an important role in mitochondria. Mitochondrial dysfunction is an important mechanism in sepsis pathophysiology. METHODS: Nintyfour Swiss Albino male mice were divided into 8 groups. CLP was performed in Group I. Coenzyme Q10, 100 mg/kg subcutaneously, was given 5 hours after CLP to Group II and 20 hours after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Similar was true in a rat model of pneumosepsis [ 60 ] and endotoxemia [ 14 ]. Antioxidant (not mitochondria targeted) treatment did not improve survival only in three mouse studies, acute pancreatitis [ 61 ], pancreatic cancer [ 62 ], and CLP [ 63 ] models. While surprising, our protracted study design (Supplementary Figure 3) allows postulating that the reduction of survival due to SkQ1 was not a coincidental observation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar was true in a rat model of pneumosepsis [ 60 ] and endotoxemia [ 14 ]. Antioxidant (not mitochondria targeted) treatment did not improve survival only in three mouse studies, acute pancreatitis [ 61 ], pancreatic cancer [ 62 ], and CLP [ 63 ] models. While surprising, our protracted study design (Supplementary Figure 3) allows postulating that the reduction of survival due to SkQ1 was not a coincidental observation.…”
Section: Discussionmentioning
confidence: 99%
“…The two recent sepsis studies offer some relevant clues regarding the antioxidant treatment timing/dosage and model severity [ 13 , 63 ]. At first, CLP mice were given a single-bolus coenzyme Q10 (strong mitochondria-targeted antioxidant) at 5 h and 20 h post-CLP.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing the antioxidant capacity (Rogobete et al, 2017) in these patients due to inefficient oxidative phosphorylation (Lorente et al, 2018) leads to an increase in free radicals (Oliveira, Pontes-de-Carvalho, Couto, & Noronha-Dutra, 2017), which is actually a possible mechanism for damage caused by the sepsis (Kumar et al, 2018). Some natural compounds and herbal derivatives have anti-inflammatory and antioxidant effects that can improve sepsis symptoms, such as zinc (Ganatra et al, 2017), magnesium (Esen et al, 2004), Q10 (Abitagaoglu et al, 2015), and curcumin (Chen, Lu, et al, 2018). Turmeric is a medicinal plant that belongs to the ginger species (Zingiberaceae), distributed throughout subtropical and tropical regions of the world, and broadly growing in Asian countries such as India and China (Yadav, Yadav, Khar, Mujeeb, & Akhtar, 2013).…”
mentioning
confidence: 99%
“…CoQ10 has been proposed as an effective agent for reducing the deleterious effects of septic shock by acting as an oxygen free radical scavenger and thus stabilizing mitochondrial membranes, as well as by inhibiting the arachidonic acid metabolic pathway and the formation of various prostaglandins. There is evidence that CoQ10 is effective in alleviating histological organ damage in sepsis via mortality statistics of mice model [26]. In addition, animal studies indicated that complex I + III activity was higher in the sepsis groups than healthy controls in septic mice models caused by lipopolysaccharide, and after treatment with Simvastatin, mitochondrial complex I + III expression was increased [27].…”
Section: Discussionmentioning
confidence: 99%